Tobacco use among rural women in reproductive age group and its association with regularity of menstrual cycles and dysmenorrhoea: a community based cross sectional study - Kulkarni, Namratha; Hawal, Nikhil; Naik, Vijaya A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco is a killer of men and women but sex specific differences exists. Along with the risk of suffering from the various health hazards from tobacco use, women are more prone to unique risks related to menstrual and reproductive function reproductive health hazards. This study was done to know the prevalence of tobacco consumption among the rural women in the reproductive age group and its association with the regularity of menstrual cycles and dysmenorrhoea. Methods: A community based cross sectional study, conducted from January 2011 to December 2011 among 1200 rural women aged between 15 years to 49 years residing in Primary Health Centre (PHC) Vantmuri area, Belgaum, Karnataka, India. Statistical analysis was done using rates, ratios and chi-square tests.. Results: The prevalence of tobacco consumption was 9.7%. 11 (10.9%) of currently pregnant women were consuming tobacco. Among the tobacco users, 89 (76.1%) had regular cycles. The association of tobacco consumption with irregular menstrual cycles was statistically significant (χ2=5.575, df=1, p=0.018). Further in this study, a very high percentage of 100 (85.5%) of the tobacco users had dysmenorrhoea. The difference was statistically strongly significant. (χ2=266.593, df=1, p<0.001). Among the tobacco users with irregular menstrual cycles, the most common manifestation was oligomenorrhoea 12 (42.9%) followed by 9 (32.1%) and 7 (25%) of menorrhagia and polymenorrhoea respectively. Conclusions: Significant association was found between tobacco consumption and the irregularity of menstrual cycles and dysmenorrhoea. It has become the need of the hour to provide enough evidence on the correlates of tobacco use in the community to assist government policy makers, health professionals and the public in developing realistic models towards effective tobacco control to cater to different sections of community in need.